Health status of pre-menarcheal and post-menarcheal adolescent girls in West Bengal, India - Pramanik, Purushottam; Banerjee, Subha Bose; Dutta, Swagata (International Journal of Research in Medical Sciences, 2017)
Background: Under nutrition in children and adolescents is a major problem in developing countries like India. Age at menarche is a significant indicator of growth in girls. There are significant differences in anthropometric and body composition characteristics between pre and post-menarcheal girls. These raised our interest to evaluate anthropometrically the health status of pre-menarcheal ad post-menarcheal girls. Methods: This study was conducted in six government schools of Bankura and Hooghly district in West Bengal state. The subjects of this study were chosen at random irrespective of socioeconomic status and religion so that reflection of an overall picture of health status of study region could be achieved. Body weight and height was measured. Body mass index (BMI) and Rohrer Index was calculated. These were compared with existing international standards for evaluation of nutritional status of the selected subjects. Student t test was used to estimate the significance of difference between pre-menarcheal and post-menarcheal girls. P<0.05 was consider as significant. Results: Significant percentage of adolescent girls was stunted, thin and underweight. Overall prevalence of stunting, thinness and underweight was 36%, 29.6% and 29.7% respectively. Percentage of all the above indices was higher in pre-menarcheal girls than post-menarcheal girls. Health status of adolescent girls was very poor. Very low health status is found to be prevalent. Conclusion: It is concluded that there is a high prevalence of under nutrition among adolescent girls. The prevalence is much more in pre-menarcheal girls than post-menarcheal counterpart. There is very high prevalence of low health status of the adolescent girls. Health education and nutrition interventions are needed on priority basis.